Post-Fire Recovery Sequence Of Black Spruce-Lichen Woodland in the Northwest Territories - Maikawa, Eugene (My University, 1976)
Tree ring analyses have been used for determining the time since the most recent fire in several areas of burned black spruce-lichen woodland on drumlins in the Northwest Territories. The vegetation on these burns has been described in detail. Analysis of the data by principal component analysis and regression analysis shows that recovery of the ground vegetation after burning follows a general sequence. Topographic factors do not appear to be of much importance. The moss Polytrichum piliferum is very abundant on burns which are less than 25 years of age. For the next 100 years the ground is almost completely covered by lichens, with Stereocaulon paschale dominating the final stages of this lichen phase. After about 150 years, the abundance of S. paschale declines rapidly and is replaced by mosses and vascular plants. This change in species composition with time is accompanied by increases in the depth of organic matter and a slow development of the spruce canopy. Control of this recovery sequence by microclimatic variables is discussed. In addition, the sequence is compared to recovery sequences which have been established for other conifer regions of Canada.
Keywords: Biology; Biology